ISLAM DAN TRADISI BARITAN - M. Mansur Syariffudin (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This paper discusses the Baritan tradition in Pemalang which isdone by the fishermen to pray for their safety. The method of interviewand observation are used to get the important data. The tradition hasbeen done in some generations as there is a syncretism between Islamand the local culture. Islamic teaching combined with the local structuremakes the praying ritual long-lasting. Still there is a diferrence in prayingfor safety mission, in the past the prayer wa intended to the Spirit whilenowadays it is intended to The Supreme God.